Sharīʻa, Islamism and Arab support for democracy. Issue 2 (17th February 2019) - Berger, Lars
ABSTRACT: The Arab Spring and its aftermath reignited the debate over the relationship between Islamism and democracy. This analysis improves upon previous research by demonstrating the crucial contribution which a more precise understanding of the multiple meanings of the concept of Sharīʻa can have on our assessment of the future of democracy in the Arab world. While support for the Sharīʻa-conformity of laws has a positive impact on the preference for democracy, the insistence that Sharīʻa represents the word of God as opposed to the human attempt to interpret it reduces support for democracy. These findings are of considerable significance for academics and policy-makers interested in the future of democracy in the Arab world as it suggests that generic expressions of support for Sharīʻa are less relevant in explaining support for democracy than what Arab women and men consider to be its essence.